Determinants of Performance of Sharia Insurance Registered at OJK - Isti Fadah; Ifon Fiyunita Putri; Lusiana Ulfa; Istatuk Budi (Universitas Muhammadiyah Yogyakarta, 2021)
Good performance is one of the company's goals, especially to get optimal profit. Profitability is determined by the income earned and the costs incurred by the company during a certain period. The profitability obtained is an accumulation of strategic decisions made by the company. Optimal profit will be able to attract investors who will invest their shares in the company. This study aims to examine and analyze the determinants of the profitability of Islamic insurance based on financial ratios. This type of research is explanatory research. The data used are secondary data with the 2015-2019 observation period. The population in this study were all sharia insurance companies registered with the Financial Services Authority (OJK). Determination of the sample in this study using purposive sampling method in order to obtain 32 samples. The proxy of the dependent variable is ROA. While the independent variable is underwriting (UND), solvency (RBC), Claims (KL), contributions or premiums (KTR). The method of data analysis in this study uses Multiple Linear Regression Analysis. The results show that underwriting and claims have a significant positive effect on the profitability of Islamic general insurance companies. solvency, and contribution (premium) have no significant effect on the profitability of Islamic general insurance companies listed in the OJK.